The Conductance and Swelling of Composite Membrane ‘Chitosan-Silver Nanoparticles’ in Monovalent Salt Solution ‘KCl and NaCl’ - Sandriani, Ni Wayan Eri; Rupiasih, Ni Nyoman; Sumadiyasa, Made (BULETIN FISIKA, 2019)
A research about to determine the conductance and water absorption capacity (swelling) of the composite membrane has been conducted. The membrane used was a membrane made of chitosan matrix, silver nanoparticle(AgNP) of 100 µg as a filler and acetic acid 1% as a solvent, which named chitosan composite membrane (Ch-AgNP). A 2% chitosan membrane (membrane Ch) used as a comparison. The membrane conductance value determined by measuring the membrane voltage (V) as a function of current (I) in monovalent salt solutions of NaCl and KCl with a concentration of 0.025 M. The swelling tests have been carried out using distilled water. The results showed that Ch membrane conductance was greater than the Ch-AgNP composite membrane. In KCl solution, the conductance is 0.0991 ? -1 and 0.0984 ? -1 and in NaCl solution are 0.1002 ? -1 and 0.0996 ? -1 . The membrane conductance is greater in NaCl solution than in KCl solution. The swelling test showed that the swelling percentage of Ch-AgNP composite membrane was greater than Ch membrane